TUTURAN IMPERATIF DALAM NOVEL BUMI CINTA KARYA HABIBURRAHMAN EL SHIRAZY - Muhammad Rafi; Charlina Charlina; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: One of the gift of the almighty God to man is language, a language that has always been used as communication media. For example is in man daily life often command others to do things according to what he wants. This act of speech is called by an imperative speech. In this study, author analyze the imperative speech in Bumi Cinta novel of Habiburrahman El Shirazy. An analytical aspect includes shape of imperative speech in Bumi Cinta novel of Habiburrahman El Shirazy. This kind of study is a qualitative research with a descriptive method. Data collection techniques used in this study are reading and recording techniques. In this study, author analyze the data by using a descriptive method to get clearly descriptions about imperative speech in Bumi Cinta novel of Habiburrahman El Shirazy. The imperative speech found in Bumi Cinta novel of Habiburrahman El Shirazy are imperative prohibition, invitation, the smooth, the emphatic, the hope, the wish, the commands, and the cross. The pragmatic imperative idea found in Bumi Cinta novel of Habiburrahman El Shirazy are the commands, the request, the cross, invitation, permits, prohibition, the hope, and the wish.Keywords: imperative speech, pragmatic imperative idea, novel.